Are regional stages necessary? - Gonzalez, Carlos Roberto (2005)
The bipartition of the Carboniferous System adopted by the International Commission of Stratigraphy for the world stratigraphic chart is impractical in Gondwana. Correlation with thePaleoequatorialrealm, from the Late Viséan to the Early Permian inclusive, is n ot possible by paleontologic means because ofendemism ofthebiota